The distribution of dissolved copper and natural organic ligands in tropical coastal waters under seasonal variation - Ng, Li Qing; Mohamed, Khairul Nizam; Amiruddin, Abd Muhaimin; Mohamat Yusuff, Ferdaus; Mustaffa, Nur Ili Hamizah (Multidisciplinary Digital Publishing Institute, 2025)
The bioavailability of dissolved copper (Cu) in seawater is influenced by the presence of natural organic matter. Changes in physicochemical conditions, such as pH, temperature, and salinity, can significantly affect the solubility and speciation of copper, thereby impacting the complexation of Cu(II)-binding organic ligands. The concentration of dissolved Cu in the coastal water of Mersing, Malaysia, was detected by anodic stripping voltammetry (ASV). The natural organic copper(II)-binding ligands (CuL) and their conditional stability constants (log K′) were determined by using the competitive ligand exchange–adsorptive cathodic stripping voltammetry method (CLE–AdCSV) in our samples. The in situ parameters, such as pH, temperature, salinity, and dissolved oxygen (DO), were found to be significantly different between sampling periods and indicated the different physical chemical conditions between the sampling periods. However, we found a consistent concentration of dissolved Cu throughout the water column between sampling periods. This suggests that the presence of a strong class of natural organic ligands (L1) in Mersing’s coastal water maintains the dissolved Cu(II) ions in the water column and prevents the scavenging and precipitation processes under the seasonal variations.